J-Shaped Association Between Respiratory Rate and In-Hospital Mortality in Acute Myocardial Infarction Patients Complicated by Congestive Heart Failure in Intensive Care Unit - Kai Zhang; Yu Shi; Yu Han; Tian Yi Cai; Fang Ming Gu; Zhao Xuan Gu; Tianqi Zhang; Mao Xun Huang (SAGE Publishing, 2024)
Background: While respiratory rate has proven to be a sensitive prognostic indicator in ICU settings, its relevance in the context of Acute Myocardial Infarction (AMI) patients complicated by Congestive Heart Failure (CHF) remains underexplored. Therefore, this study aims to investigate the relationship between respiratory rate and in-hospital mortality in this specific patient cohort. Methods: This retrospective cohort study utilized the Medical Information Mart for Intensive Care-IV database to analyze all AMI patients with concomitant CHF. The primary outcome, in-hospital mortality, was assessed through multivariate analysis. Logistic regression models, restricted cubic spline regression models, and subgroup analyses were employed to explore the association between respiratory rate and in-hospital mortality. Results: The study encompassed 5056 participants diagnosed with both CHF and AMI. After adjusting for confounding variables, each incremental unit rise in respiratory rate was associated with an 8% increase in the risk of patient mortality (OR = 1.08, 95% CI: 1.05∼1.11, P < 0.001). When comparing individuals with respiratory rates in the first tertile (≤17 breaths per minute) and the third tertile (>17-20 breaths per minute) to those in the second tertile (17-20 breaths per minute), the adjusted ORs for in-hospital mortality were 1.09 (95% CI: 0.82∼1.46, P = 0.546) and 1.62 (95% CI: 1.27∼2.06, P < 0.001), respectively. A dose-response relationship depicted a J-shaped curve between respiratory rate and the risk of in-hospital mortality, with an inflection point at approximately 19 breaths per minute. Stratified analyses confirmed the robustness of this correlation. Conclusions: This study reveals a J-shaped association between respiratory rate and in-hospital mortality in ICU patients suffering from both AMI and CHF.